2013
DOI: 10.1177/197140091302600410
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty and Stenting of Symptomatic Vertebral Artery Stenosis Clinical and Angiographic Follow-up of 206 Cases from Northwest Iran

Abstract: SUMMARY -Percutaneous transluminal angioplasty (PTA) has recently become a noteworthy treatment option for significant stenosis involving the vertebral artery (VA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The use of EPDs has been described in several studies involving angioplasty and stenting of lesions of a VA origin [1,5,7,9,10,12,13,14]. To date, newer or alternative methods for cerebral protection for the treatment of vertebrobasilar (VB) stenosis have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of EPDs has been described in several studies involving angioplasty and stenting of lesions of a VA origin [1,5,7,9,10,12,13,14]. To date, newer or alternative methods for cerebral protection for the treatment of vertebrobasilar (VB) stenosis have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerotic disease is a major cause of ischemic events worldwide [1,2,3]. Posterior circulation strokes comprise approximately 20-25% of all strokes of ischemic origin.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammadian et al (2013) reported a 15.9% restenosis rate in a 2-y series of 206 patients who underwent percutaneous trans-luminal angioplasty or stenting to treat VA stenosis in all segments (V1-V4). This result is similar to that in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…In our study all lesions were treated with stents as primary stenting has been shown to improve long-term patency compared with balloon procedures alone [ 11 , 12 ]. Despite higher rates of restenosis as compared to other treatment options, balloon angioplasty may be considered in patients who are unable to tolerate open surgery and/or with contraindications to dual-antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 99%